The Relationship between Left Ventricular Function Indices in Tissue Doppler Imaging and Exaggerated Blood Pressure Response During the Exercise Stress Test: - Ghaderi, Fereshteh; Hemati, Milad; Gholoobi, Arash; Eshraghi, Ali; Sadeghi Allah Abadi, Javad (Galen Medical Journal, 2020)
Background: Studies have indicated that exaggerated hypertension during activity and stress can be a good predictor of the incidence of hypertension. This study tries to evaluate left ventricular (LV) function by tissue Doppler to assess early changes in ventricular compliance before the onset of Hypertension (HTN) in patients with exaggerated blood pressure response during the exercise test. Materials and Methods: In this case-control study, 40 patients without a history of hypertension with systolic blood pressure less than 140/90 which referred for exercise test, were included. The exercise test was performed for all patients. Patients who had exaggerated blood pressure during the stress test were considered as cases and the controls with normal blood pressure responses. Then standard echocardiography and Tissue Doppler imaging performed and indices of LV systolic and diastolic were recorded. Results: The LV mass in cases and controls were 174.9±50.78 and 152.9±33.59, respectively (P=0.114), and LV mass index in cases and controls were 127.4±13.5 and 79.8±15.75, respectively (P=0.023). Moreover, the LV Myocardial Performance Index were 0.68±0.11 and 0.48±0.06 in cases and controls, respectively (P<0.001). The heart rate, E/A, EE, E Velocity and S velocity were measuremented. Except E/A (P=0.009), there was no significant difference between the other variables measured between the cases and controls (P>0.05). Conclusion: The results of this study showed that using 2D conventional echocardiography as a noninvasive method if performed in prestigious centers can evaluate systolic and diastolic function Tissue Doppler parameters very well in the early stages of heart disease caused by HTN. [GMJ.2020;9:e1323]